Religion, ethnicity and transnational migration between West Africa and Europe - Grodź, Stanisław.; Smith, Gina Gertrud. (Muslim Minorities, 2014)
Religion, Ethnicity and Transnational Migration between West Africa and Europe focuses on the West African migrants' presence in Europe and the way they negotiate religion and ethnicity in a new context. Special attention is given to the diversity of religious background of the migrants and to exploration of interreligious (especially Christian-Muslim) relations. These dimensions of transnational migration have not been widely researched, yet. After introducing the new African religious diaspora, the situation of the Senegalese, Ghanaian and Fulbe migrants - both Christian and Muslim - in France, Spain, the Netherlands, Germany and Switzerland is analysed. The impact the migrants make on their communities of origin in Africa is also taken into account. Contributors are: Afe Adogame, Martha Frederiks, Stanisław Grodź, Tilmann Heil, Monika Salzbrunn, José C.M. van Santen, Miriam Schader, Etienne Smith and Gina Gertrud Smith.